Revitalization of the Kota Tua Area in Supporting Sustainable Tourism in Cirebon District - Muhamad, Muhamad; Kardiyati, Endah Nurhawaeny (Prasetiya Mulya Publishing, 2025)
The revitalization and rejuvenation of Kota Tua urgently requires the role of local stakeholders in a sustainable manner. The study aims to see how revitalization can preserve the city's cultural heritage, preserve historical values, and develop the economic sector. The study is in the Kota Tua area, Jamblang, Cirebon. The study method uses qualitative descriptive analysis techniques. The study emphasizes field phenomena as well as indicators of sustainable tourism development. Indicators used in connection with this study are a) sites, b) local culture, c) historical buildings, d) area landscapes, and e) community participation in conservation. These indicators have varying levels of importance and quality in Cirebon. The revitalization and rejuvenation of the Kota Tua has a high level of importance and quality in Cirebon.